Exporting Australian higher education: future strategies in a maturing market - Mazzarol, T.; Hosie, Peter (MCB University Press, 1996)
Examines the current situation facing Australian higher education institutions engaged in the export of their services. Considers current trends in the world market for international education services, as well as current and future developments in the Australian higher education system. Recent research evidence suggests that the international market for education is reaching maturity. Contends that Australia’s international education sector, especially in the area of higher education, requires greaterdifferentiation and more careful marketing in order to deal with this trend. Outlines some suggestions as to appropriate future strategies for the Australian international education sector.